Impact of the Pandemic Covid-19 on Kosovo Businesses: Array - Livoreka, Besnik; Haziri, Artan (Acta Universitatis Danubius. Œconomica, 2021)
The research tends to identify the impact of the COVID-19 pandemic, on economic life and businesses in Kosovo. Which was the effect of the isolation measure, business closures, reduced working hours, and the other government measures in business and economic life in Kosovo. The data for this scientific paper were collected through an online questionnaire which was compiled in order to extract first-hand data and then based on the analysis to show and present scientific data on how the pandemic has affected economic life. After the completion of the work, we will try to give a new overview of how we have reacted as a state to this extraordinary situation to maintain economic health, how it has affected businesses, which types of businesses have been less affected, which types of businesses will come out of the industry, what types of businesses will change activity, what types of businesses will thrive.